Structural and optical properties of lithium sodium borate glasses doped with Sm3+ ions - Dawaud, R. S. E. S.; Hashim, Suhairul; Alajerami, Yasser Saleh Mustafa; Mhareb, M. H. A.; Maqableh, Mazin M.; Tamchek, Nizam (World Scientific Publishing, 2014)
Absorption and emission spectra of Sm3+ doped lithium sodium borate (LNB) have been reported. The samples were prepared by the melt-quenching technique and characterized by X-ray diffraction (XRD), diffraction thermal analysis (DTA), Fourier transforms infrared (FTIR) spectroscopy and field emission scanning electron microscopy (FESEM). From the thermo-grams spectrum, glass transition (Tg), crystallization (Tc) and melting temperatures (Tm) have been evaluated. Direct and indirect optical band gaps have been calculated based on the glasses UV absorption spectra. These glasses have shown strong nine absorption bands with hypersensitive transition at 1221 nm (6H5/2→4H3/2) and five emission bands for the transition at 4I7/2→6H13/2 (green color), 4I7/2→6H7/2 (orange color), 4I7/2→6H9/2 (orange color), 4I7/2→6H11/2 (red color) and 4I7/2→6H13/2 (red color) with performing an excitation of 400 nm. The oscillator strengths, refractive index, ions concentration, polaron radius and other parameters have been calculated for each dopant.